The Garden Intrigue - Willig, Lauren (New York : Dutton, 2012)
An atrocious poet teams up with an American widow to prevent Napoleon's invasion of England.
Keywords: Napoleon -- I, -- Emperor of the French, -- 1769-1821 -- Fiction; Poets, English. -- Fiction; Widows -- Fiction; Americans -- Fiction -- France; Undercover operations -- Fiction; Paris (France) -- Fiction -- Social life and customs -- 19th century; Romantic suspense fiction; Regency fiction; Spy stories